“New Kids on the Block?” Reappraising Pottery Styles, aDNA, and Chronology from Western Iberia Early Neolithic - Diniz, Mariana (2022)
Western Iberia Early Neolithic has been described as an ultimate and very altered form of the Mediterranean Neolithisation process. Despite its Atlantic position, this territory – corresponding mainly to Central/Southern Portugal – is, in its physical and cultural geography, a Mediterranean landscape deeply connected to a historical process arriving from beyond the Strait of Gibraltar. The presence of cardial pottery led archaeologists to ascribe Portuguese Early Neolithic to a Mediterranean impressed Pottery cultural area, and according to demic diffusion models, small pioneer groups carrying the Neolithic package originated there. Recently, the archaeological record for the Western Mediterranean Neolithisation is becoming more complex and longer lasting cardial dominance over the seas has been disputed. Previous Neolithic groups seafaring the Mediterranean coasts with Impressa style pottery could have reached Iberian Peninsula by 5600–5400 cal BC, proving that by the mid-sixth millennium, different cultural entities were moving in the Western Mediterranean regardless of their genetic features. The main goal of this study is to disclose this cultural diversity in Western Iberia using a robust chronological database and debating how different proxies, like pottery styles and ancient DNA (aDNA), reveal it in Western Iberia. While recognising the Mediterranean input to Western Iberia groups, mapping the variability and the significance of different decoration techniques, such as cardial, false acacia leaf, impressed stripes, and using the aDNA to identify continuities/changes in ancient populations are here as tools to understand when, who, and how new kids came to the block. To do so, different disciplinary boundaries are crossed, and some transdisciplinary critical aspects are also commented.